Southern man eaudiobook A novel. - Iles, Greg (Penn Cage, 2024)
"Greg Iles is one of America's great storytellers. –Stephen King, #1 New York Times bestselling author ?""A first-rate political thriller."" – John Grisham, #1 New York Times bestselling author The hugely anticipated new Penn Cage novel from the #1 New York Times bestselling author of the Natchez Burning trilogy and Cemetery Road, about a man—and a town—rocked by anarchy and tragedy, but unbowed in the fight to save those they love Fifteen years after the events of the Natchez Burning trilogy, Penn Cage is alone. Nearly all his loved ones are dead, his old allies gone, and he carries a mortal secret that separates him from the world. But Penn's exile comes to an end when a brawl at a Mississippi rap festival triggers a bloody mass shooting—one that nearly takes the life of his daughter Annie. As the stunned cities of Natchez and Bienville reel, antebellum plantation homes continue to burn and the deadly attacks are claimed by a Black radical group as historic acts of justice. Panic sweeps through the tourist communities, driving them inexorably toward a race war. But what might have been only a regional sideshow of the 2024 Presidential election explodes into national prominence, thanks to the stunning ascent of Robert E. Lee White, a Southern war hero who seizes the public imagination as a third-party candidate. Dubbed "the Tik-Tok Man," and funded by an eccentric Mississippi billionaire, Bobby White rides the glory of his Special Forces record to an unprecedented run at the White House—one unseen since the campaign of H. Ross Perot. To triumph over the national party machines, Bobby evolves a plan of unimaginable daring. One fateful autumn weekend, with White set to declare his candidacy in all fifty states, the forces polarizing America line up against one another: Black vs. white, states vs. the federal government, democracy vs. Fascism. Teaming with his fearless daughter (now a civil rights lawyer) and a former Black Panther who spent most of his life in Parchman Prison, Penn tears into Bobby White's pursuit of the Presidency and ultimately risks a second Civil War to try to expose its motivation to the world, before the America of our Constitution slides into the abyss. In Southern Man, Greg Iles returns to the riveting style and historic depth that made the Natchez Burning trilogy a searing masterpiece and hurls the narrative fifteen years forward into our current moment—where America itself teeters on the brink of anarchy.